TREATMENT OF ANEMIA AND IMPROVEMENT OF QUALITY OF LIFE AMONG PATIENTS WITH CROHN'S DISEASE: experience using ferric carboxymaltose - SOBRADO,Carlos Walter (2015)
Objectives - Anemia is the most common hematological alteration in patients with Crohn's disease, and is frequently related to intestinal inflammatory activity. Its cause is multifactorial and mostly associated with absolute iron deficiency (iron deficiency anemia) and/or functional iron deficiency (inflammation anemia or anemia of chronic disease). It may also be identified through other causes, such as folic acid or vitamin B12 deficiency and secondary to adverse effects from medications (salicylic derivatives and immunosuppressive drugs). In the present study, patients with active Crohn's disease and anemia were evaluated and treated with intravenous ferric carboxymaltose. We discuss the therapeutic schemes (doses), safety, results and improvement of quality of life. Methods - In the present prospective study, 10 consecutive patients with Crohn's disease, with moderate to severe activity, with anemia (Hb: 6.7 to 10 g/dL), who were attended between March 2014 and March 2015, were evaluated. Six (60%) were men and four were women, all with moderate or severe anemia (hemoglobin <10 g/dL). They were treated with a maximum of three intravenous infusions of 1000 mg of ferric carboxymaltose, of at least 15 minutes in duration. It was also sought to correlate the inflammatory Crohn's disease activity degree (measured using the Crohn's Disease Activity Index, CDAI) and C-reactive protein level with the severity of anemia. The primary outcome was an increase in Hb of ≥2 g/dL and the secondary outcome was the normalization of anemia (Hb ≥12 g/dL for women and ≥13 g/dL for men) and the improvement in quality of life seen 12 weeks after the last application of carboxymaltose. Results - Among the 10 patients studied, parenteral iron supplementation was administered in three cases during hospitalization and the others received this on an outpatient basis. The total iron dose ranged from 1,000 to 2,000 mg, with an average of 1,650 mg. Crohn's disease activity measured using CDAI and C-reactive protein correlated with the intensity of anemia. An increase of 2 g/dL occurred in eight (80%) patients after 12 weeks and normalization of anemia was found in seven (70%) patients. Improvements in quality-of-life scores were found for all (100%) patients after 12 weeks. Carboxymaltose was well tolerated. Three patients presented adverse reactions (two with nausea and one with headache) of mild intensity. Conclusions - Anemia is a frequent complication for Crohn's disease patients. Intravenous iron therapy has been recommended for Crohn's disease patients, because for these patients, oral iron absorption is very limited. This is because of the inflammatory state and "blocking" of iron entry into enterocytes through hepcidin action on ferroportin, along with the elevated rates of gastrointestinal adverse events that compromise adherence to treatment and possibly aggravate the intestinal inflammatory state. The degree of Crohn's disease activity, as measured using CDAI and C-reactive protein, correlates with the severity of anemia. Carboxymaltose is a safe drug, which can be administrated in high doses (up to 1,000 mg per application per week) and corrects anemia and iron stocks over a short period of time, with consequent improvement in quality of life.